An unusual cause of multiple foot ulcers in a patient with type 2 diabetes - Elmalti, Akrem; Elgzyri, Targ; Varghese, Shiby; Mukhtar, Mamoun (Ibnosina Journal of Medicine and Biomedical Sciences, 2020)
Diabetes is the most common cause of nontraumatic lower limb amputation. The majority of those amputations are preceded by an ulcer, usually as a result of peripheral neuropathy, peripheral vascular disease, or a combination of both. Regular foot examination and multi-disciplinary team approach are supported by evidence as tools to reduce foot ulceration. A cause for foot ulceration is not always evident, but presumed trauma or burn are usually thought. We are presenting a rather unusual case of a 70-year-old patient with long-standing diabetes and peripheral sensory neuropathy who first presented with bilateral superficial foot ulcers. On follow-up visits, further new superficial multiple ulcers were discovered and a possibility of rat bite was raised which he and his family denied. His daughter later confirmed the sighting of rodent biting his flesh. Rodent bites causing foot ulcers are rare; however, the clinician's vigilance is key for the early detection and treatment.
Keywords: Diabetes; foot ulcer; peripheral neuropathy; rat bite